Associations Between Time to Administration of Antiseizure Medications and Short-Term Clinical Outcomes in Adults With Status Epilepticus - Kongsakorn, Pongsakorn; Boongird, Apisit (Ramathibodi Medical Journal, 2024)
Background: Status epilepticus (SE) is a time-sensitive emergency that requires immediate treatment. Objective: To analyze the associations between time to administration of antiseizure medications (ASM) and short-term clinical outcomes. Methods: From January 1, 2014, to December 31, 2020, we performed a retrospective cohort study in adult patients who presented with SE. The primary objective was to analyze the association between the timing of ASM administration and mortality. The second and third objectives were to determine the relationship between the timing of ASM administration and length of hospital stay along with the modified Rankin Scale (mRS) at discharge, respectively. Results: A total of 83 patients were enrolled. The mean age was 57 years. The mean length of hospital stay was 32 days. Benzodiazepine (BDZ) was prescribed as the first ASM in 79 (95.2%) patients. Levetiracetam was the second most frequently administered ASM (39, [47%]), followed by phenytoin (28 [33.7%]) and valproate (13 [15.7%]). Seventy-one patients (85.5%) had a seizure duration longer than t2 period. Therapy delay in SE and underdosing of ASM were noted in both alive and dead groups. Although the mortality rate was 20.5% and was highest in super-refractory SE (15 [88.2%]), we found no statistically significant difference between in-hospital mortality and timing of ASM administration. For secondary outcomes, including length of hospital stay and mRS, a statistically significant finding was only noted in the category of timing of seizure onset to the first ASM (P = .002 and P = .004, respectively). Conclusions: This study showed no significant association between timing of ASM administration and in-hospital mortality. Prolonged duration of SE tends to be associated with increased mortality. SE guidelines were not followed in a substantial proportion of SE patients.